1997
DOI: 10.1046/j.1526-4610.1997.3707455.x
|View full text |Cite
|
Sign up to set email alerts
|

Migrainelike Headache in a Patient With a Hemorrhagic Pituitary Macroadenoma

Abstract: A 23-year-old woman presented with a 4-day history of a severe migrainelike headache with a normal neurologica examination. The headache resolved after a ketorolac injection, but recurred a few hours later. An MRI scan of the brain showed a hemorrhagic pituitary macroadenoma for which she underwent transsphenoidal removal of the tumor 1 month later. Although uncommon, pituitary hemorrhage with and without apoplexy should be considered in the differential diagnosis of acute headache. Pituitary hemorrhage can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Seven of the 18 studies found that 46/103 patients (44%) described a significant or complete resolution of HA from medications such as anti‐emetics and nonsteroidal anti‐inflammatory drugs (NSAIDs) (Table 1). Five were case reports 14‐18 . Two articles, one retrospective and the other prospective, described relief of HA from simple or common analgesics 19,20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the 18 studies found that 46/103 patients (44%) described a significant or complete resolution of HA from medications such as anti‐emetics and nonsteroidal anti‐inflammatory drugs (NSAIDs) (Table 1). Five were case reports 14‐18 . Two articles, one retrospective and the other prospective, described relief of HA from simple or common analgesics 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…In all the studies, the HAs had secondary causes including subarachnoid hemorrhage (SAH), subdural hematoma, intracranial hemorrhage, meningitis, cerebral venous sinus thrombosis (CVST), pituitary adenoma, and brain tumor. In 4 of the studies, 7 patients had a delay in the real diagnosis by hours to weeks, at least in part, because of a misinterpretation of the favorable response to analgesics 14‐16,18 …”
Section: Resultsmentioning
confidence: 99%
“…There have been a few other cases of pituitary apoplexy that presented with migraine like headache, including ophthalmoplegic migraine like headache . Evans, in 1997, also described a 23‐year‐old woman with a 4‐day history of severe migraine‐like headache who had similar MRI findings of a hemorrhagic pituitary microadenoma …”
Section: Discussionmentioning
confidence: 99%
“…Whether patients with first time migraine need investigation can only be answered with the rather unhelpful “it depends.” A confident diagnosis (as here) does not warrant investigation, but more abrupt presentations (“crash migraine”) certainly do, as we know clinical features alone are insufficient to help us differentiate the benign from the sinister in acute onset headache syndromes, 3 and that some rare pathologies may mimic migraine 10 . Similarly, the presence of focal neurological symptoms/signs, unless very typically of an evolving migrainous nature, are likely to trigger at least a brain scan.…”
mentioning
confidence: 88%